Smooth muscle ATP-sensitive potassium channels mediate migraine-relevant hypersensitivity in mouse models. (February 2022) - Christensen, Sarah L; Rasmussen, Rikke H; Cour, Sanne La; Ernstsen, Charlotte; Hansen, Thomas F; Kogelman, Lisette JA; Lauritzen, Sabrina P; Guzaite, Gintare; Styrishave, Bjarne; Janfelt, Christian; Christensen, Søren T; Aziz, Qadeer; et al.
Background: Opening of KATP channels by systemic levcromakalim treatment triggers attacks in migraine patients and hypersensitivity to von Frey stimulation in a mouse model. Blocking of these channels is effective in several preclinical migraine models. It is unknown in what tissue and cell type KATP -induced migraine attacks are initiated and which KATP channel subtype is targeted. Methods: In mouse models, we administered levcromakalim intracerebroventricularly, intraperitoneally and intraplantarily and compared the nociceptive responses by von Frey and hotplate tests. Mice with a conditional loss-of-function mutation in the smooth muscle KATP channel subunit Kir6.1 were given levcromakalim and GTN and examined with von Frey filaments. Arteries were tested for their ability to dilate ex vivo . mRNA expression, western blotting and immunohistochemical stainings were made to identify relevant target tissue for migraine induced by KATP channel opening. Results: Systemic administration of levcromakalim induced hypersensitivity but central and local administration provided antinociception respectively no effect. The Kir6.1 smooth muscle knockout mouse was protected from both GTN and levcromakalim induced hypersensitivity, and their arteries had impaired dilatory response to the latter. mRNA and protein expression studies showed that trigeminal ganglia did not have significant KATP channel expression of any subtype, whereas brain arteries and dura mater primarily expressed the Kir6.1 + SUR2B subtype. Conclusion: Hypersensitivity provoked by GTN and levcromakalim in mice is dependent on functional smooth muscle KATP channels of extracerebral origin. These results suggest a vascular contribution to hypersensitivity induced by migraine triggers.